Effect of dihydropyridine calcium channel blockers on blood pressure variability in the SPRINT trial: a treatment effects approach. Issue 3 (21st March 2022) - de Havenon, Adam; Petersen, Nils; Wolcott, Zoe; Goldstein, Eric; Delic, Alen; Sheibani, Nazanin; Anadani, Mohammad; Sheth, Kevin N.; Lansberg, Maarten; Turan, Tanya; Prabhakaran, Shyam
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Increased visit-to-visit blood pressure variability (vvBPV) has negative effects on multiple organ systems. Prior research has suggested that dihydropyridine calcium channel blockers (CCB) may reduce vvBPV, which we attempted to verify in a high-quality dataset with robust statistical methodology. Methods: We performed a post hoc analysis of the SPRINT trial and included participants who were on a dihydropyridine CCB either 0 or 100% of follow-up study visits. The primary outcome was vvBPV, defined as residual standard deviation (rSD) of SBP from month 6 until study completion. We estimated the average treatment effect of the treated (ATET) after augmented inverse-probability-weighting (AIPW) matching. Results: Of the 9361 participants enrolled in SPRINT, we included 5020, of whom 1959 were on a dihydropyridine CCB and 3061 were not; mean age was 67.4 ± 9.2 years, 34.5% were men, 65.9% were white, 49.4% were randomized to intensive blood pressure control, and the rSD was 10.1 ± 4.0 mmHg. Amlodipine represented greater than 95% of dihydropyridine CCB use. After AIPW matching of demographics and other antihypertensive medications, the ATET estimation for participants on a dihydropyridine CCB was an rSD that was 2.05 mmHg lower (95% CI −3.19 to −0.91). We did not find that other antihypertensive medications classes decreased vvBPV, and several increased it. Conclusion: In the SPRINT trial, consistent use of a dihydropyridine CCB was associated with a 2 mmHg reduction in vvBPV. The implication of this hypothesis-generating finding in a high-quality dataset is that future trials to reduce vvBPV could consider using dihydropyridine CCBs.